Digital Close Range Photogrammetry (DCRP) in façade recording and 3D as-built mappping for cultural heritage building / Abd. Manan Samad, Mat Rahim Ibrahim and Saiful Aman Sulaiman - Samad, Abd. Manan; Ibrahim, Mat Rahim; Sulaiman, Saiful Aman (Research Management Institute (RMI), 2013)
The proposed research study is focus on the significant to contribute to the Malaysia in cultural heritage conservation where the data can be used in re-build the buildings or objects. It will also prepared for engineers and others professionals in the field of construction and heritage conservation for their reference. The scope of this research study will be focusing on comparing the methods in cultural heritage recording with conventional method and Digital Close Range Photogrammetry (DCRP). The process of recording only involve the outside structure, the interior structure not be included. Since the public is getting more concerned about conservation of cultural heritage features, it is predictable that more will make use of 3D models to explain their projects as 3D would provide excellent visual appreciation of the spatial relationship of structures with existing environment and to record historical features to facilitate future maintenance and restoration works. Other than that, the result can be used as a reference for the future generation and very precious as Lorn Acton stated: “Ultimate history we cannot have in this generation, but we can dispose of conventional history, and show the point we have reached on the road from one to the other, now that all information is within reach, and every problem has become capable of solution.”